Measuring User Satisfaction in Website Usability by Considering Stress Level - Raka, Surya Jaya; Setyohadi, Djoko Budiyanto (JOIV : International Journal on Informatics Visualization, 2021)
Usability testing, part of the human-computer interaction problem, is a method commonly used to evaluate the performance of a website interface. Today's study of human-computer interaction is important. It is now developed into UI UX (User Interface / User Experience). The website interface can affect user satisfaction and is a principal factor in a website being liked by users and meeting user needs. When a website is first developed, it can be difficult for a developer to understand the need for a website interface that matches the user persona of that website. Therefore, this research is important as an evaluation material for websites that are developed in the context of a website interface to provide a satisfactory appearance according to user personas. This study evaluates a website by conducting a usability test using the ISO-9241 aspect and getting an average result of 50,967, which is categorized as a bad website is taken from all users in the experiment. This study can also prove the psychological factors of users that influence usability testing, namely differences in the perceptions of website ratings between users with normal and (mild, moderate, severe, too severe) psychological stress levels. Users with normal stress levels will have better usability test results than users with stress levels. This study shows better results than user ratings with a normal stress level of 73,750, so it is categorized as a reliable website.